Pengembangan Program Baca Tulis Al-Quran dalam Memaksimalkan Pendidikan Agama Islam Tingkat Sekolah Dasar - Dimas Agustiwa; Ahmad Alim; Ibdalsyah Ibdalsyah (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2026)
Students who can read the Quran well tend to understand Islamic Religious Education material more easily than those who still have difficulty reading the hijaiyah letters. Good teaching not only focuses on reading skills but also trains students to write Quranic verses correctly according to Arabic writing rules (Muhammad et al., 2025). The Quranic reading ability of elementary school students remains very concerning, according to official data from the Ministry of Religious Affairs of the Republic of Indonesia. The results of the 2025 Islamic Religious Education (PAI) assessment showed that the Quranic reading index of PAI teachers at elementary/special needs schools was 58.26 percent, followed by elementary school students at 51.17 percent. Elementary school students are still not fluent in reading the Quran or are still in the pratama or basic category. A total of 3,251,617 fifth-grade students across Indonesia participated in tests and questionnaires through the Ministry of Religious Affairs' SIAGA application (Adian Husaini, 2026). Based on this background, a program that would maximize Islamic Religious Education (BTQ-PAI) is needed. This research employed the Research and Development (R&D) method with the ADDIE model. Program needs analysis was conducted by creating a Google Form with a closed-ended questionnaire, which was then distributed randomly to respondents. Program design was carried out after analyzing existing programs from leading schools. After the design was neatly formulated, it was validated by experts and implemented by users. The final stage was a feasibility test by experts, who provided a rating for the developed program. The feasibility test results indicated that the Integrated BTQ-PAI Phase C Elementary School program could be used to maximize Islamic Religious Education in schools.